A perspective-taking model for global assignments - Hyung Park, Joon; Lea Abbott, Je’Anna; Werner, Steve (Emerald Publishing Group, 2013)
Purpose:The purpose of this paper is to propose a model that explains how proactive cognitive processes, such as perspective-taking, relates to expatriates’ effectiveness. Design/methodology/approach: This conceptual paper presents the model that is based on the perspective-taking models developed by Parker et al. (2008) and applies them to the expatriate context. Findings: The authors present a framework that delineates how the perspective-taking process leads to an expatriate’s effectiveness. The authors provide propositions about which factors motivate expatriates to engage in perspective-taking and which factors influence higher accuracy of understanding of the host country nationals’ (HCN) perspective. Practical implications: Guidance is provided for the training of expatriate to develop perspective-taking. Originality/value: The paper expands the expatriate research by incorporating the perspective-taking model to identify which factors may motivate expatriates to see the HCN view point. Also, the paper contributes to the literature by identifying how resources such as expatriates’ psychological capital may promote the degree of accuracy or comprehension with respect to the HCN thoughts and feelings.